Penerapan Etika Bisnis Pada Produk Tabungan Haji Shafa Mudharabah Di Bank BPD DIY Cabang Syariah (Analisis Berdasarkan Keputusan Munas Tarjih Dan Tajdid Muhammadiyah Ke 26 Tentang Etika Bisnis) - Prima Sanjaya; Mardiana Susanti; Mhd Lailan Arqam (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Islamic business ethics is a standard derived from the Al-Qur’an and Hadith which is used as a guide in actions, behavior and comparisons between good and bad in business. Ethics and economics cannot be separated from human life, even economics is a common activity in the lives of everyday citizens. The purpose of this study was to analyze the business ethics of the Haji Shafa Mudharabah Savings product at the BPD DIY Bank Yogyakarta Sharia Branch and to find out whether the Islamic business ethics applied to Bank BPD DIY Yogyakarta Sharia Branch are in accordance with the business ethics decisions of the Majlis Tarjih and Tajdid Muhammadiyah or not. This study uses a descriptive qualitative approach. Data collection was carried out at Bank BPD DIY Yogyakarta Syariah Branch. Data collection techniques by document study and data analysis using qualitative methods. Data analysis used reduction, display, verification and conclusions. The results of this study indicate that the application of business ethics carried out by Bank BPD DIY Syariah, especially in the Haji Shafa Mudharabah Savings product, has been going well. Meanwhile, in relation to the application of business ethics at the 26th National Congress Tarjih and Tajdid Muhammadiyah Decision on Business Ethics, it can be concluded that Bank BPD DIY Syariah has complied with the decision